Assessing the influence of the cultural perspective on cross cultural conflict: An analysis of cultural environment - Faiza Akhtar; Suleman Aziz Lodhi; Safdar Shah Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Globalization has opened new doors of business opportunities for organizations, but at the same time it has transformed the working environment into a highly multicultural setup. Accordingly the issue of understanding and handling multi-culturalism effectively is gaining importance in organizations. The paper explores the influence of cultural intangibles in multicultural organization while highlighting a new role of "enhanced understanding of cultural diversity" that would reduce team conflict for better group performance. Mixed methods paradigm is used for developing a framework to analyze horizontal and vertical links and core factors contributing towards cross cultural conflicts in a multi-cultural environment. The sample consisted of 427 participants. The findings show that the potential for conflict is intrinsically embedded in multi-culture teams due to difference in cultural frame of reference used by corresponding individuals. The study further indicates that language compatibility, and misapprehensions of cultural differences are the main contributors towards conflict.
Keywords: 330; multi-culturalism; multi-cultural organization; work environment; conflict; cultural diversity; cultural non-materials aspects; organizational behavior